Molecular basis of human essential hypertension. - Sadiqa Syed; Masood A Qureshi (Journal of Bahria University Medical and Dental College)
Essential hypertension (HTN) affects over one billion people worldwide. It is a complex, multifactorial, quantitative trait under polygenic control resulting from inheritance of a number of susceptibility genes and involves multiple environmental determinants in different combinations in different individuals. The completion of the draft sequence of human genome and recent advances in the genetics have resulted in identification and characterization of various genetic mechanisms that associate increased blood pressure and cardiovascular risk factors. The possible molecular mechanisms involved in homeostasis, ranging from locally acting vasoactive peptides to components of rennin angiotensin aldosterone system to epithelial sodium channels and sodium chloride transporters have been discussed. Several vasoregulatory systems including sympathetic vasoregulation and cytokines release have been studied extensively. Despite all these efforts of identification of numerous candidate genes in different ethnic populations using different approaches and technologies, the results are still inconsistent and the genetic and molecular basis of HTN remains unclear. In view of rapid availability of useful data on various aspects of Physiology and genetics of HTN, it is pertinent to review such information focusing on association of well known candidate genes with various facets of HTN and their physiological regulatory processes. Thus HTN related risk factors, known to have interactions with genes are highlighted in this article.